A Study on the Design of Nozzles with a High Air Entrainment Ratio - Ozkan, F.; Onay, Begum Kantarci; Baylar, A. (Sciendo, 2025)
When a water jet passes through a layer of air and plunges into a pool of water, it is well known that it entrains a significant amount of air into the pool. This forms a submerged, two-phase region with a large surface area at the air-water interface. This process is called plunging water jet entrainment and aeration. This paper describes an experimental study of the air entrainment ratio of two-hole circular nozzles. Depending on which air holes were opened on the circular nozzles, negative pressure was created. The resulting aeration of the jet affected its expansion, shape, and roughness; consequently, it also affected the air entrainment ratio. The investigation showed that the maximum air entrainment ratio was achieved with a nozzle length four times the diameter of the nozzle. Higher air entrainment ratios were observed for air holes with diameters greater than 2 mm. Additionally, a design equation was developed to estimate the air entrainment ratio of two-hole circular nozzles. This equation considers the ratio of the nozzle diameter to the air hole diameter, the water jet length, the circular nozzle length, and the jet velocity at the nozzle inlet.
Keywords: air entrainment; nozzle; two-phase flow; water jet